Salt-assisted inner and outer double-layer carbon-coated silicon material, preparation method and application thereof

Through the preparation method of salt-assisted internal and external double-layer carbon-covered silicon material, the structural problems caused by volume expansion of silicon materials in lithium-ion batteries are solved, the cycle stability and rate performance of the battery are improved, and the production cost is reduced. It is suitable for large-scale Large-scale production.

CN119191269APending Publication Date: 2024-12-27WUHAN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411407244.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, volume expansion of silicon material during lithiation and deliquification leads to structural damage and instability of electrode interfaces. Although double-layer or multi-layer carbon-clad materials can alleviate volume expansion, they increase costs and may introduce lithium. Ion transmission is hindered, and uniformity and quality control are difficult, which affects battery performance.

Method used

The preparation method of salt-assisted internal and external double-layer carbon-covered silicon material is prepared by using multiple liquid phase coating and inorganic salt template technology, combined with rapid heating and short-term annealing treatment, and prepared core-shell structure silicon material with internal and external double-layer carbon-covered , control the thickness of the carbon layer and the amount of inorganic salt added to ensure the structural stability and electrochemical properties of the material.

Benefits of technology

It has achieved improvements in the structural stability and electrochemical performance of silicon materials, reduced production costs and safety risks, is suitable for large-scale commercial production, and improved the cycle stability and rate performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191269A_ABST
    Figure CN119191269A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion battery materials, and relates to a salt-assisted inner and outer double-layer carbon-coated silicon material, a preparation method and application thereof, and the preparation method comprises the following steps: S1, preparing a single-layer carbon inner-coated silicon material C (at) Si; s2, filling pores with inorganic salt; s3, preparing an outer carbon coating layer; s4, carrying out pre-carbonization in an inert atmosphere; s5, washing in an aqueous solution, and drying; and S6, performing high-temperature carbonization in an inert atmosphere to obtain the salt-assisted inner and outer double-layer carbon-coated silicon material C (at) Si (at) C. The silicon material with a special core-shell structure prepared in a salt-assisted inner and outer double-layer carbon coating mode is used as a lithium ion battery negative electrode material, the electrochemical performance of the material can be improved, and the conductivity, the chemical stability and the safety are improved; and the preparation method is simple, the process is short, the preparation temperature is low, the potential safety hazard in the preparation process is low, the raw materials are cheap and easy to obtain, and the production cost can be saved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion battery materials, and in particular relates to a salt-assisted inner and outer double-layer carbon-coated silicon material, a preparation method and an application thereof. Background Art

[0002] With the continuous pursuit of electric vehicle range and portable electronic device usage time, the market demand for high energy density batteries is growing. Silicon has an extremely high theoretical specific capacity (about 4200 mAh / g), which is much higher than traditional graphite anode materials (about 372 mAh / g), making it an ideal choice for improving battery energy density. However, silicon undergoes significant volume expansion (about 300%) during lithiation and delithiation, which can lead to material structure destruction and electrode interface instability. To solve this problem, researchers have developed a variety of silicon-based composite materials, such as silicon-carbon composites, porous silicon, and silicon nanostructures to improve structural stability and cycle life. The development of nanotechnology and material synthesis technology has enabled researchers to design and manufacture silicon-based anode materials with optimized structure and performance. The volume expansion problem of silicon during charge and discharge can be effectively alleviated by precisely controlling the nanostructure of the material. The electrochemical stability and cycle performance of silicon anodes can be improved by forming a stable coating or interface layer on the silicon surface, such as a carbon coating, an oxide coating, etc.

[0003] Coating silicon materials with carbon layers is currently one of the most effective and commonly used methods to alleviate silicon volume expansion. Carbon materials have high electrical conductivity. By introducing a carbon layer on the silicon surface, the overall electrical conductivity of the electrode can be improved, thereby improving the charge and discharge performance of the battery. The carbon layer can act as a protective layer to reduce the direct contact between silicon and the electrolyte, thereby reducing the occurrence of side reactions and improving the cycle stability and safety of the battery. At the same time, by precisely controlling the thickness and structure of the carbon layer, the porosity and surface area of ​​the material can be optimized, thereby improving the lithium ion transmission rate and the rate performance of the battery. However, although the carbon layer can alleviate the volume expansion of silicon, under long-term cycling or high temperature conditions, the interface between the carbon layer and the silicon core may degrade, and silicon will contact the electrolyte again, affecting the cycle stability; at the same time, blindly increasing the thickness of the carbon layer to improve the structural stability will result in a higher irreversible capacity loss, and the charge and discharge performance of the material will still be limited.

[0004] At present, double-layer carbon or multi-layer carbon-coated silicon materials have appeared, which can more effectively buffer the volume expansion and contraction of silicon during charging and discharging, reduce stress concentration, and thus improve the structural stability and cycle life of electrode materials. The outer carbon layer can provide additional electron transmission channels, reduce the internal resistance of the battery, and improve the charge and discharge efficiency and rate performance of the battery. Multi-layer carbon layers can more effectively isolate the direct contact between silicon and the electrolyte, reduce the occurrence of side reactions, and reduce the decomposition of the electrolyte, thereby improving the chemical stability and safety of the battery. It also helps to form a more stable solid electrolyte interface (SEI), reduce the continuous SEI formation and maintenance costs, and improve the long-term cycle stability of the battery. However, compared with single-layer carbon coating, double-layer or multi-layer carbon coating may increase the overall cost of the material; multi-layer carbon coating may introduce more interfaces, which may become obstacles to lithium ion transmission, affecting the rate performance and charge and discharge efficiency of the battery; at the same time, it is a challenge to ensure the uniformity and quality of each layer of carbon coating, and uneven carbon layers may cause inconsistent and rapid attenuation of battery performance. To overcome these shortcomings, researchers are also constantly optimizing material design, synthesis processes and battery manufacturing technologies to improve the performance of double-layer or multi-layer carbon-coated silicon materials, reduce costs, and ensure their reliability and safety in practical applications. Summary of the invention

[0005] In view of the deficiencies of the above-mentioned prior art, the present invention provides a salt-assisted inner and outer double-layer carbon-coated silicon material, a preparation method and application thereof. The specific technical scheme is as follows: The first object of the present invention is to provide a method for preparing a salt-assisted inner and outer double-layer carbon-coated silicon material, comprising the following steps: S1: The silicon material is dispersed evenly using an alcohol solution containing an organic carbon source, and then heated at a constant temperature under negative pressure. After the alcohol solvent is completely evaporated, it is cooled to room temperature and taken out to obtain a single-layer carbon-encapsulated silicon material (C@Si) that has not been carbonized at high temperature. S2: placing the uncarbonized single-layer carbon-encapsulated silicon material obtained in S1 in an aqueous solution containing an inorganic salt and dispersing the material uniformly; then heating the material at a constant temperature under negative pressure until the aqueous solvent is completely evaporated, cooling the material to room temperature and taking the material out; S3: The substance obtained in S2 is dispersed evenly with an alcohol solution containing an organic carbon source, and then heated at a constant temperature under negative pressure until the alcohol solvent is completely evaporated, cooled to room temperature and taken out; S4: placing the material obtained in S3 into a tube furnace, pre-carbonizing it under an inert atmosphere, and cooling it to room temperature after the heat preservation is completed and taking it out; S5: washing and drying the substance obtained in S4 in an aqueous solution; S6: The material obtained in S5 is placed in a tubular furnace, and subjected to high-temperature carbonization under an inert atmosphere. After heat preservation, the material is cooled to room temperature and then taken out to obtain a salt-assisted inner and outer double-layer carbon-coated silicon material (C@Si@C).

[0006] The present invention prepares a special core-shell structured silicon material by salt-assisted inner and outer double-layer carbon coating, wherein the inner core is silicon and the inner shell is a carbon layer tightly wrapped on the silicon surface, which can provide an electron conduction channel, improve the conductivity of the material, and alleviate volume expansion; the outer shell completely wraps the entire structure, which can block the erosion of the electrolyte, provide better structural stability, and retain the internal pores of silicon, which is essential for the transmission and storage of lithium ions. The preparation method of the present invention is simple, the process is short, and the safety hazard is low; the raw materials are cheap and easy to obtain, the cost is low, and it is conducive to large-scale commercial production.

[0007] Furthermore, the silicon material is one of nano silicon, silicon nanowire and porous silicon.

[0008] Furthermore, in S1 and S3, the organic carbon source is one of compounds such as glucose, citric acid, phenolic resin, urea, etc.; preferably phenolic resin.

[0009] Furthermore, in S1 and S3, the amount of the organic carbon source added is 2-20% of the mass of the silicon material; preferably 3-15%; more preferably 5-10%; and most preferably 5%.

[0010] The present invention controls the thickness of the inner and outer carbon coating layers by controlling the amount of organic carbon source added. If the thickness of the inner carbon coating layer is low, it cannot effectively buffer the volume expansion of silicon during the charge and discharge process, thereby affecting the structural stability and cycle life of the material; if the thickness of the inner carbon coating layer is too high, it will hinder the transmission of lithium ions, increase the internal resistance of the battery, and affect the charge and discharge rate and rate performance of the battery. If the thickness of the outer carbon coating layer is low, it cannot effectively protect the inner silicon and inner carbon, causing the silicon particles to be exposed to the electrolyte, increasing the risk of side reactions; if the thickness of the outer carbon coating layer is too high, the excessively thick outer carbon may increase the overall weight and volume of the material, thereby reducing the energy density of the battery, and also hindering the transmission of lithium ions; therefore, the control of the amount of organic carbon source added in the present invention is extremely important.

[0011] Furthermore, in S1 and S3, the temperature of the constant temperature heating is 60-100°C, preferably 70-90°C, and more preferably 80°C.

[0012] Furthermore, in S2, the inorganic salt is one of compounds such as sodium chloride, potassium chloride, sodium carbonate, potassium carbonate, etc.; preferably sodium chloride.

[0013] Furthermore, in S2, the added amount of the inorganic salt is 10-40% of the mass of the silicon material; preferably 20-30%; more preferably 25%.

[0014] The present invention fills the pores by adding inorganic salts. If the amount of inorganic salt added is too little, the pores of the carbon-silicon material cannot be completely filled, leaving insufficient expansion space for the internal structure. If the amount of inorganic salt added is too much, in addition to filling all the pores, excess inorganic salt will adhere to the surface and form voids after washing. Although the expansion space is increased, the diffusion path of lithium ions will be lengthened, affecting the electrochemical performance. Therefore, control of the amount of inorganic salt added is extremely important in the present invention.

[0015] Furthermore, in S2, the temperature of the constant temperature heating is 80-120°C, preferably 90-110°C, and more preferably 100°C.

[0016] Furthermore, in S4, the pre-carbonization temperature is 300-600°C, preferably 400-550°C, and more preferably 500°C.

[0017] Furthermore, in S4, the temperature rise rate of the pre-carbonization is 0.1-20°C / min; preferably 2-10°C / min; further preferably 5-10°C / min; more preferably 5°C / min.

[0018] Furthermore, in S4, the insulation time is 10-180 min, preferably 30-90 min, and more preferably 60 min.

[0019] The selection of the pre-carbonization temperature and the holding time is extremely critical in the present invention. If the pre-carbonization temperature is too low and the holding time is too short, the structure of the outer carbon layer is not stable enough and will be destroyed during water washing, causing the internal structure to be exposed to the electrolyte, affecting the electrochemical performance; if the pre-carbonization temperature is too high and the holding time is too long, the molten salt effect of the inorganic salt will accelerate the oxidation of silicon, seriously affecting the reversible charge and discharge specific capacity and reducing the energy density of the battery; therefore, the control of the pre-carbonization temperature and the holding time is extremely important in the present invention.

[0020] Furthermore, in S5, the washing temperature is 60-120°C, preferably 80-100°C, and more preferably 90°C.

[0021] Furthermore, in S5, the washing time is 2-6 h, preferably 3-5 h, and more preferably 4 h.

[0022] The selection of water washing temperature and time is very important in the present invention. If the water washing temperature is too low and the water washing time is too short, the inorganic salts cannot be completely washed away and remain in the pores, which can neither enhance the structural stability nor affect the capacity. If the water washing temperature is too high and the water washing time is too long, the chemical composition and physical properties of the material surface may be changed, thereby affecting its compatibility with the electrolyte. Therefore, the selection of water washing temperature and time is extremely important in the present invention.

[0023] Furthermore, in S6, the temperature of the high temperature carbonization is 700-1200°C, preferably 800-1000°C, and more preferably 900°C.

[0024] Furthermore, in S6, the heating rate of the high temperature carbonization temperature is 0.1-20°C / min; preferably 2-10°C / min; further preferably 5-10°C / min; more preferably 5°C / min.

[0025] Furthermore, in S6, the insulation time is 10-180 min; preferably 120-180 min; more preferably 150 min.

[0026] The selection of the heating rate, carbonization temperature and holding time for high-temperature carbonization is very important in the present invention. A too low heating rate may cause the material to stay at high temperature for too long, resulting in a dense structure of the carbon coating layer, which is not conducive to the migration of lithium ions; a too high heating rate may cause uneven temperature distribution inside the material, causing thermal stress, thereby affecting the structural integrity and performance of the material. Too low a carbonization temperature may lead to incomplete carbonization, and more non-carbon elements will remain in the material, affecting its electrical conductivity and chemical stability; too high a carbonization temperature may cause excessive graphitization of the material. Although the electrical conductivity is improved, the mechanical properties and flexibility of the material may be sacrificed. Too short a holding time may lead to insufficient carbonization reaction and poor material performance; too long a holding time may lead to excessive pyrolysis of the material, resulting in too many defects and structural collapse, affecting the mechanical strength and electrochemical properties of the material.

[0027] The second object of the present invention is to provide a salt-assisted inner and outer double-layer carbon-coated silicon material, which is prepared by the above-mentioned preparation method.

[0028] The present invention uses multiple liquid-phase coatings, uses inorganic salts as templates and then washes them away to retain pores, and uses rapid heating and short-time annealing treatment to obtain a double-layer carbon-coated silicon material at low temperature (below 1200°C). The silicon material is used as a negative electrode material for lithium-ion batteries and can improve the electrochemical properties of the material.

[0029] The third object of the present invention is to provide a negative electrode material, comprising the above-mentioned salt-assisted inner and outer double-layer carbon-coated silicon material.

[0030] The beneficial effects of the present invention are: The present invention prepares a silicon material with a special core-shell structure by means of salt-assisted inner and outer double-layer carbon coating. Silicon particles are embedded in a matrix composed of two layers of carbon. The inner carbon layer is in direct contact with the silicon core, providing an electron transmission channel and improving the conductivity. The outer carbon layer can protect the inner carbon layer and the silicon core from the erosion of the electrolyte, reduce side reactions, and improve the chemical stability and safety of the battery. The inner and outer double-layer carbon layers can more effectively buffer the volume expansion of silicon during the charge and discharge process, reduce the cracking and pulverization of the structure, and thus improve the cycle stability of the electrode. In addition, the preparation method of the present invention is simple, the process is short, and the preparation temperature is low. The potential safety hazard in the preparation process is low. The raw materials of the present invention are cheap and easy to obtain, which is conducive to saving production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 XRD patterns of single-layer carbon-coated porous silicon (C@pSi) and salt-assisted inner and outer double-layer carbon-coated porous silicon material (C@pSi@C) according to Example 1 of the present invention; Figure 2 The scanning electron microscope images of C@pSi and C@pSi@C of Example 1 of the present invention; (a) is a scanning electron microscope image of salt-assisted inner and outer double-layer carbon-coated porous silicon material; (b) is a scanning electron microscope image of a porous silicon material encapsulated in a single layer of carbon; Figure 3 TEM images of C@pSi and C@pSi@C of Example 1 of the present invention; (a) Transmission electron microscopy image of salt-assisted inner and outer double-layer carbon-coated porous silicon material; (b) is a transmission electron microscope image of a porous silicon material encapsulated in a single layer of carbon; Figure 4 Electrochemical cycle performance diagrams of porous silicon (pSi), single-layer carbon-coated porous silicon (C@pSi), and salt-assisted inner and outer double-layer carbon-coated porous silicon material (C@pSi@C) according to Example 1 of the present invention; Figure 5 The rate performance diagrams of porous silicon (pSi), single-layer carbon-coated porous silicon (C@pSi), and salt-assisted inner and outer double-layer carbon-coated porous silicon material (C@pSi@C) of Example 1 of the present invention are shown; Figure 6 The first coulombic efficiency diagram of porous silicon (pSi), single-layer carbon-coated porous silicon (C@pSi) and salt-assisted inner and outer double-layer carbon-coated porous silicon material (C@pSi@C) of Example 1 of the present invention; Figure 7 This is a graph of the electrochemical cycle performance of the salt-assisted inner and outer double-layer carbon-coated porous silicon material (C@pSi@C) of Comparative Example 1 of the present invention; Figure 8This is a graph of electrochemical cycle performance of the salt-assisted inner and outer double-layer carbon-coated porous silicon material (C@pSi@C) of Comparative Example 2 of the present invention; Fig. 9 This is a graph of electrochemical cycle performance of the salt-assisted inner and outer double-layer carbon-coated porous silicon material (C@pSi@C) of Comparative Example 3 of the present invention; Fig.10 This is a graph of electrochemical cycle performance of the salt-assisted inner and outer double-layer carbon-coated nano-silicon material (C@nSi@C) of Comparative Example 4 of the present invention; Fig.11 This is a graph of the electrochemical cycle performance of the salt-assisted inner and outer double-layer carbon-coated silicon nanowire material (C@wSi@C) of Comparative Example 5 of the present invention; Fig.12 This is a morphology diagram of the inner and outer double-layer carbon-coated porous silicon material (C@pSi@C) of Comparative Example 6 of the present invention; Fig.13 This is a cycle performance diagram of the inner and outer double-layer carbon-coated porous silicon material (C@pSi@C) of comparative example 6 of the present invention. DETAILED DESCRIPTION

[0032] The principles and features of the present invention are described below in conjunction with embodiments. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention. Example

[0033] A method for preparing a salt-assisted inner and outer double-layer carbon-coated silicon material comprises the following steps: (1) Porous silicon with a particle size of 3-5 μm was selected as the raw material, and an alcohol solution containing 5% of the mass of the porous silicon in phenolic resin was used to disperse the porous silicon uniformly. The alcohol solvent was completely evaporated at 80 °C and -0.1 MPa, and then the porous silicon material (C@pSi) was obtained by cooling to room temperature. (2) The sample obtained in (1) was evenly dispersed in an aqueous solution containing 25% of the mass of porous silicon sodium chloride, and the aqueous solvent was completely evaporated at 100°C and -0.1 MPa, and then cooled to room temperature and taken out; (3) The sample obtained in (2) is dispersed evenly in an alcohol solution containing phenolic resin with a mass percentage of 5% of the porous silicon, and the alcohol solvent is completely evaporated at 80 °C and -0.1 MPa, and then cooled to room temperature and taken out; (4) Place the sample obtained in (3) in a tube furnace, heat it to 500 °C at a heating rate of 5 °C / min in an Ar atmosphere for pre-carbonization, and keep it at this temperature for 60 min. After the end of the heat preservation, cool it to room temperature and take it out; (5) Place the sample obtained in (4) into an aqueous solution, wash it with water at 90 °C for 4 h, filter it, and dry it; (6) The sample obtained in (5) was placed in a tubular furnace and heated to 900 °C at a heating rate of 5 °C / min in an Ar atmosphere for high-temperature carbonization. The temperature was kept at this temperature for 150 min, and the sample was cooled to room temperature and taken out to obtain a salt-assisted inner and outer double-layer carbon-coated porous silicon negative electrode material C@pSi@C.

[0034] Experimental Results Figure 1 Figure 2 is the XRD pattern of single-layer carbon-coated porous silicon material (C@pSi) and salt-assisted inner and outer double-layer carbon-coated porous silicon material (C@pSi@C). C@pSi and C@pSi@C have the same peak position. The broad diffraction peaks at 28.5°, 47.3°, 56.2°, 69.2°, 76.5° and 87.9° are assigned to the (111), (220), (311), (400), (331) and (442) planes of the Si cubic phase. Figure 1 In addition to the pure silicon phase, no other phases were detected, but the peak of C@pSi@C was weaker than that of C@pSi. This is because the amorphous carbon content in C@pSi@C is higher, and the corresponding silicon content will be lower, and the peak will be weaker. No other substances were detected, indicating that no impurities were introduced in the entire process.

[0035] Figure 2 The figures are scanning electron microscope images of C@pSi@C and C@pSi, where (a) is a scanning electron microscope image of a salt-assisted inner and outer double-layer carbon-coated porous silicon material, and (b) is a scanning electron microscope image of a single-layer carbon-coated porous silicon. The salt-assisted inner and outer double-layer carbon-coated porous silicon material prepared in this embodiment has two layers of amorphous carbon wrapped around porous silicon. The inner layer of amorphous carbon-coated porous silicon has a three-dimensional cross-linked porous structure like the porous silicon raw material, indicating that the amorphous carbon coating layer has not changed the morphology of the porous silicon and has a uniformly distributed porous structure, which is conducive to the entry of the electrolyte and shortens the transmission path of lithium ions. The outer layer of amorphous carbon coating layer completely wraps the internal structure, which can improve the conductivity while blocking the erosion of the internal structure by the electrolyte, further alleviating the volume expansion of silicon and reducing the pulverization of the material.

[0036] Figure 3 The transmission electron micrographs of C@pSi@C and C@pSi, where (a) is a transmission electron micrograph of a salt-assisted inner and outer double-layer carbon-coated porous silicon material. The outer carbon layer completely wraps the inner single-layer carbon-coated porous silicon, effectively preventing the internal structure from rupturing and causing the reaction between silicon and the electrolyte. At the same time, the internal pore structure is retained, which is beneficial to the transmission of lithium ions and leaves more expansion space for the internal structure. (b) is a transmission electron micrograph of a single-layer carbon-coated porous silicon. The pores inside the interconnected skeleton can be clearly observed. The inner-coated carbon layer tightly wraps the porous silicon skeleton, significantly improving the conductivity of the porous silicon, alleviating the volume expansion to a certain extent, and having better electrochemical performance.

[0037] Figure 4 Figure 2 is the electrochemical cycle performance diagram of pSi, C@pSi and C@pSi@C. After 3 cycles at a current density of 0.1 A / g, C@pSi@C exhibits more stable cycle performance than pSi and C@pSi for a long time at a current density of 1 A / g. Although the reversible specific capacity will be slightly reduced due to the presence of the carbon layer in the early stage, the structure of C@pSi@C is more stable. At a current density of 1 A / g, C@pSi@C still retains a reversible specific capacity of 1462 mAh / g after 500 cycles, and the capacity retention rate is 77.2% (compared with the 4th cycle), while C@pSi only retains a reversible specific capacity of 1030 mAh / g after 500 cycles, and the capacity retention rate is 55.4% (compared with the 4th cycle). pSi only retains a reversible specific capacity of 774 mAh / g after 500 cycles, and the capacity retention rate is 35.04% (compared with the 4th cycle), reflecting the better cycle stability of C@pSi@C.

[0038] Figure 5 This is the rate performance diagram of pSi, C@pSi and C@pSi@C. After cycling for 5 cycles at current densities of 0.1, 0.2, 0.5, 1, 2, and 5 A / g, and then returning to a current density of 0.1 A / g for 5 cycles, C@pSi@C shows a higher discharge specific capacity, which means that it shows faster electron and ion transfer capabilities, and therefore has better rate performance.

[0039] Figure 6 The first coulomb efficiency diagram of pSi, C@pSi and C@pSi@C. The first efficiency of pSi is 81.06%. Although the carbon coating does not provide capacity, it can greatly improve the conductivity of silicon, which is beneficial to lithium ion transfer. Under the combined effect of these two effects, the first efficiency of C@pSi is slightly higher than that of porous silicon, at 81.99%. The first efficiency of C@pSi@C is slightly lower than that of C@pSi, at 80.1%.

[0040] Comparative Example 1 A method for preparing a salt-assisted inner and outer double-layer carbon-coated silicon material comprises the following steps: (1) Select porous silicon with a particle size of 3-5 μm as the raw material, and evenly disperse it with an alcohol solution containing 1% of the mass of porous silicon phenolic resin. Wait for the alcohol solvent to be completely evaporated at 80 °C and -0.1 MPa, and cool it to room temperature before taking it out; (2) The sample obtained in (1) was evenly dispersed in an aqueous solution containing 25% of the mass of porous silicon sodium chloride, and the aqueous solvent was completely evaporated at 100°C and -0.1 MPa, and then cooled to room temperature and taken out; (3) The sample obtained in (2) is dispersed evenly in an alcohol solution containing phenolic resin with a mass percentage of 5% of the porous silicon, and the alcohol solvent is completely evaporated at 80 °C and -0.1 MPa, and then cooled to room temperature and taken out; (4) Place the sample obtained in (3) in a tube furnace, heat it to 500 °C at a heating rate of 5 °C / min in an Ar atmosphere for pre-carbonization, and keep it at this temperature for 60 min. After the end of the heat preservation, cool it to room temperature and take it out; (5) Place the sample obtained in (4) into an aqueous solution, wash it with water at 90 °C for 4 h, filter it, and dry it; (6) The sample obtained in (5) was placed in a tubular furnace and heated to 900 °C at a heating rate of 5 °C / min in an Ar atmosphere for high-temperature carbonization. The temperature was kept at this temperature for 150 min, and the sample was cooled to room temperature and taken out to obtain a salt-assisted inner and outer double-layer carbon-coated porous silicon negative electrode material C@pSi@C.

[0041] Figure 7 This is the electrochemical cycling performance diagram of C@pSi@C (the amount of phenolic resin added as the inner carbon source is 1% of the mass of porous silicon). Its first efficiency is 76.4%. At the same time, at a current density of 1 A / g, the reversible specific capacity after 500 cycles is 1391 mAh / g, and the capacity retention rate is 71.8% (compared with the 4th cycle).

[0042] In this embodiment, the amount of phenolic resin added during carbon coating is too low, resulting in a low thickness of the inner carbon coating layer, which cannot effectively alleviate the volume expansion of silicon and directly leads to the rupture of the inner carbon coating layer.

[0043] Comparative Example 2 A method for preparing a salt-assisted inner and outer double-layer carbon-coated silicon material comprises the following steps: (1) Select porous silicon with a particle size of 3-5 μm as the raw material, and evenly disperse it with an alcohol solution containing 5% of the mass of the porous silicon phenolic resin. Wait for the alcohol solvent to be completely evaporated at 80 °C and -0.1 MPa, and cool it to room temperature before taking it out; (2) Disperse the sample obtained in (1) evenly in an aqueous solution containing 50% of the mass of porous silicon sodium chloride, wait for the water solvent to be completely evaporated at 100°C and -0.1 MPa, cool to room temperature and take out; (3) The sample obtained in (2) is dispersed evenly in an alcohol solution containing phenolic resin with a mass percentage of 5% of the porous silicon, and the alcohol solvent is completely evaporated at 80 °C and -0.1 MPa, and then cooled to room temperature and taken out; (4) Place the sample obtained in (3) in a tube furnace, heat it to 500 °C at a heating rate of 5 °C / min in an Ar atmosphere for pre-carbonization, and keep it at this temperature for 60 min. After the end of the heat preservation, cool it to room temperature and take it out; (5) Place the sample obtained in (4) into an aqueous solution, wash it with water at 90 °C for 4 h, filter it, and dry it; (6) The sample obtained in (5) was placed in a tubular furnace and heated to 900 °C at a heating rate of 5 °C / min in an Ar atmosphere for high-temperature carbonization. The temperature was kept at this temperature for 150 min, and the sample was cooled to room temperature and taken out to obtain a salt-assisted inner and outer double-layer carbon-coated porous silicon negative electrode material C@pSi@C.

[0044] Figure 8 This is the electrochemical cycling performance diagram of PC / C / p-Si (the amount of sodium chloride added is 50% of the mass of porous silicon). Its first efficiency is 69.9%. At the same time, at a current density of 1 A / g, the reversible specific capacity after 500 cycles is 917.8 mAh / g, and the capacity retention rate is 69.6% (compared with the 4th cycle).

[0045] In this embodiment, a large amount of sodium chloride is added, resulting in a surplus of sodium chloride while filling the pores, which is attached to the surface of the particles. After being washed away, the pores become larger than before, and the transmission path of lithium ions between the two carbon layers becomes longer, resulting in an adverse effect on the electrochemical performance.

[0046] Comparative Example 3 A method for preparing a salt-assisted inner and outer double-layer carbon-coated silicon material comprises the following steps: (1) Select porous silicon with a particle size of 3-5 μm as the raw material, and evenly disperse it with an alcohol solution containing 5% of the mass of the porous silicon phenolic resin. Wait for the alcohol solvent to be completely evaporated at 80 °C and -0.1 MPa, and cool it to room temperature before taking it out; (2) The sample obtained in (1) was evenly dispersed in an aqueous solution containing 25% of the mass of porous silicon sodium chloride, and the aqueous solvent was completely evaporated at 100°C and -0.1 MPa, and then cooled to room temperature and taken out; (3) The sample obtained in (2) is dispersed evenly in an alcohol solution containing 1% of the mass of porous silicon phenolic resin, and the alcohol solvent is completely evaporated at 80 °C and -0.1 MPa, and then cooled to room temperature and taken out; (4) Place the sample obtained in (3) in a tube furnace, heat it to 500 °C at a heating rate of 5 °C / min in an Ar atmosphere for pre-carbonization, and keep it at this temperature for 60 min. After the end of the heat preservation, cool it to room temperature and take it out; (5) Place the sample obtained in (4) into an aqueous solution, wash it with water at 90 °C for 4 h, filter it, and dry it; (6) The sample obtained in (5) was placed in a tubular furnace and heated to 900 °C at a heating rate of 5 °C / min in an Ar atmosphere for high-temperature carbonization. The temperature was kept at this temperature for 150 min, and the sample was cooled to room temperature and taken out to obtain a salt-assisted inner and outer double-layer carbon-coated porous silicon negative electrode material C@pSi@C.

[0047] Fig. 9 This is the electrochemical cycling performance diagram of C@pSi@C (the amount of phenolic resin added as the outer carbon source is 1% of the mass of porous silicon). Its first efficiency is 81.86%. At the same time, at a current density of 1 A / g, the reversible specific capacity after 500 cycles is 1255 mAh / g, and the capacity retention rate is 64.4% (compared with the 4th cycle).

[0048] In this embodiment, the amount of phenolic resin added during the outsourcing is too low, which directly leads to the outsourcing carbon layer being too thin, unable to alleviate the expansion of the internal structure during the cycle, and thus unable to maintain structural stability and break, affecting the electrochemical performance of C@pSi@C.

[0049] Comparative Example 4 A method for preparing a salt-assisted inner and outer double-layer carbon-coated silicon material comprises the following steps: (1) Select nano-silicon particles with a particle size of 10-500 nm as raw materials, use an alcohol solution containing 5% of the mass of nano-silicon to evenly disperse them, wait for the alcohol solvent to be completely evaporated at 80 ° C and -0.1 MPa, and cool to room temperature before taking out; (2) Disperse the sample obtained in (1) evenly in an aqueous solution of sodium chloride containing 25% by mass of nano-silicon, wait for the water solvent to be completely evaporated at 100°C and -0.1 MPa, cool to room temperature and take out; (3) The sample obtained in (2) was dispersed evenly in an alcohol solution containing phenolic resin with a mass percentage of 5% nano-silicon, and the alcohol solvent was completely evaporated at 80 °C and -0.1 MPa, and then cooled to room temperature and taken out; (4) Place the sample obtained in (3) in a tube furnace, heat it to 500 °C at a heating rate of 5 °C / min in an Ar atmosphere for pre-carbonization, and keep it at this temperature for 60 min. After the end of the heat preservation, cool it to room temperature and take it out; (5) Place the sample obtained in (4) into an aqueous solution, wash it with water at 90 °C for 1 h, filter it, and dry it; (6) The sample obtained in (5) is placed in a tubular furnace and heated to 900 °C at a heating rate of 5 °C / min in an Ar atmosphere for high-temperature carbonization. The temperature is kept at this temperature for 150 min, and the sample is cooled to room temperature and taken out to obtain a salt-assisted inner and outer double-layer carbon-coated nano-silicon negative electrode material C@nSi@C.

[0050] Fig.10 This is the electrochemical cycling performance diagram of C@nSi@C (washed with water for 1 h). Its first efficiency is 74.18%. At the same time, at a current density of 1 A / g, the reversible specific capacity is 1005 mAh / g after 500 cycles, and the capacity retention rate is 70.2% (compared with the 4th cycle).

[0051] In this embodiment, the water washing time is short, and the sodium chloride is not completely removed, remaining in the two carbon layers, which seriously affects the reversible capacity of C@nSi@C. Although the structure is stable, the electrochemical performance is greatly reduced.

[0052] Comparative Example 5 A method for preparing a salt-assisted inner and outer double-layer carbon-coated silicon material comprises the following steps: (1) Silicon nanowires with a diameter of 10-500 nm are selected as raw materials, and are evenly dispersed in an alcohol solution containing 5% of the mass of phenolic resin of the silicon nanowires. The alcohol solvent is completely evaporated at 80 °C and -0.1 MPa, and then cooled to room temperature and taken out; (2) The sample obtained in (1) was evenly dispersed in an aqueous solution containing 25% of the mass of silicon nanowires in sodium chloride, and the aqueous solvent was completely evaporated at 100 °C and -0.1 MPa, and then cooled to room temperature and taken out; (3) The sample obtained in (2) was evenly dispersed in an alcohol solution containing 5% of the mass of silicon nanowires in a phenolic resin, and the alcohol solvent was completely evaporated at 80 °C and -0.1 MPa, and then cooled to room temperature and taken out; (4) Place the sample obtained in (3) in a tube furnace, heat it to 500 °C at a heating rate of 5 °C / min in an Ar atmosphere for pre-carbonization, and keep it at this temperature for 60 min. After the end of the heat preservation, cool it to room temperature and take it out; (5) Place the sample obtained in (4) into an aqueous solution, wash it with water at 90 °C for 4 h, filter it, and dry it; (6) The sample obtained in (5) was placed in a tubular furnace and heated to 700 °C at a heating rate of 5 °C / min under an Ar atmosphere for high-temperature carbonization. The temperature was kept at this temperature for 180 min, and the sample was cooled to room temperature and taken out to obtain a salt-assisted inner and outer double-layer carbon-coated silicon nanowire negative electrode material C@wSi@C.

[0053] Fig.11 This is the electrochemical cycling performance diagram of C@wSi@C (temperature 700 ℃, insulation 180 min), its first efficiency is 76.61%. At the same time, at a current density of 1 A / g, the reversible specific capacity after 500 cycles is 1252 mAh / g, and the capacity retention rate is 72.4% (compared with the 4th cycle).

[0054] The high-temperature carbonization heat treatment temperature in this embodiment is relatively low. Although the insulation time is prolonged, as the reaction temperature decreases, a very complete outer carbon coating layer cannot be obtained, and a portion of the internal structure will be exposed in the electrolyte. Continuous reactions will cause the SEI to break and regenerate, forming "dead lithium".

[0055] Comparative Example 6 A method for preparing a salt-assisted inner and outer double-layer carbon-coated silicon material comprises the following steps: (1) Select porous silicon with a particle size of 3-5 μm as the raw material, and evenly disperse it with an alcohol solution containing 5% of the mass of the porous silicon phenolic resin. Wait for the alcohol solvent to be completely evaporated at 80 °C and -0.1 MPa, and cool it to room temperature before taking it out; (2) The sample obtained in (1) was evenly dispersed in an aqueous solution containing 25% of the mass of porous silicon sodium chloride, and the aqueous solvent was completely evaporated at 100°C and -0.1 MPa, and then cooled to room temperature and taken out; (3) The sample obtained in (2) is dispersed evenly in an alcohol solution containing phenolic resin with a mass percentage of 5% of the porous silicon, and the alcohol solvent is completely evaporated at 80 °C and -0.1 MPa, and then cooled to room temperature and taken out; (4) Place the sample obtained in (3) into an aqueous solution, wash it with water at 90 °C for 4 h, filter it, and dry it; (5) The sample obtained in (4) was placed in a tubular furnace and heated to 900 °C at a heating rate of 5 °C / min under an Ar atmosphere for high-temperature carbonization. The temperature was kept at this temperature for 150 min, and the sample was cooled to room temperature and taken out to obtain a salt-assisted inner and outer double-layer carbon-coated porous silicon negative electrode material C@pSi@C.

[0056] Fig.12 This is the morphology of C@pSi@C (without pre-carbonization). Since no pre-carbonization was carried out and the carbon coating was directly washed with water, the carbon coating was not stable and some of the carbon layers fell off with the removal of sodium chloride. Therefore, C@pSi and C@pSi@C can be clearly distinguished. The particles without porous morphology are C@pSi@C, and the particles with porous morphology are C@pSi.

[0057] Fig.13 This is the cycle performance diagram of C@pSi@C (without pre-carbonization). Its first efficiency is 69.77%. At the same time, at a current density of 1 A / g, the reversible specific capacity after 500 cycles is 1146 mAh / g, and the capacity retention rate is 72.1% (compared with the 4th cycle).

[0058] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a salt-assisted inner and outer double-layer carbon-coated silicon material, characterized in that: The steps include: S1: The silicon material is dispersed evenly using an alcohol solution containing an organic carbon source, and then heated at a constant temperature under negative pressure. After the alcohol solvent is completely evaporated, it is cooled to room temperature and taken out to obtain a single-layer carbon-encapsulated silicon material C@Si that has not been carbonized at high temperature; S2: placing the uncarbonized single-layer carbon-encapsulated silicon material obtained in S1 in an aqueous solution containing an inorganic salt and dispersing the material uniformly; then heating the material at a constant temperature under negative pressure until the aqueous solvent is completely evaporated, cooling the material to room temperature and taking the material out; S3: The substance obtained in S2 is dispersed evenly with an alcohol solution containing an organic carbon source, and then heated at a constant temperature under negative pressure until the alcohol solvent is completely evaporated, cooled to room temperature and taken out; S4: placing the material obtained in S3 into a tube furnace, pre-carbonizing it under an inert atmosphere, and cooling it to room temperature after the heat preservation is completed and taking it out; S5: washing and drying the substance obtained in S4 in an aqueous solution; S6: The material obtained in S5 is placed in a tubular furnace, and subjected to high-temperature carbonization in an inert atmosphere. After heat preservation, the material is cooled to room temperature and then taken out to obtain a salt-assisted inner and outer double-layer carbon-coated silicon material C@Si@C.

2. The method for preparing the salt-assisted inner and outer double-layer carbon-coated silicon material according to claim 1, characterized in that: The silicon material is one of nano silicon, silicon nanowire and porous silicon.

3. The method for preparing the salt-assisted inner and outer double-layer carbon-coated silicon material according to claim 1, characterized in that: In S1 and S3, the organic carbon source is one of glucose, citric acid, phenolic resin and urea; and the added amount of the organic carbon source is 2-20% of the mass of the silicon material.

4. The method for preparing the salt-assisted inner and outer double-layer carbon-coated silicon material according to claim 1, characterized in that: In S2, the inorganic salt is one of sodium chloride, potassium chloride, sodium carbonate and potassium carbonate; the added amount of the inorganic salt is 10-40% of the mass of the silicon material.

5. The method for preparing the salt-assisted inner and outer double-layer carbon-coated silicon material according to claim 1, characterized in that: In S4, the pre-carbonization temperature is 300-600°C; the pre-carbonization temperature rise rate is 0.1-20°C / min; and the insulation time is 10-180 min.

6. The method for preparing the salt-assisted inner and outer double-layer carbon-coated silicon material according to claim 1, characterized in that: In S5, the washing temperature is 60-120° C. and the washing time is 2-6 h.

7. The method for preparing the salt-assisted inner and outer double-layer carbon-coated silicon material according to claim 1, characterized in that: The temperature of the high-temperature carbonization is 700-1200°C; the heating rate of the high-temperature carbonization temperature is 0.1-20°C / min; and the insulation time is 10-180 min.

8. The method for preparing the salt-assisted inner and outer double-layer carbon-coated silicon material according to claim 1, characterized in that: In S1 and S3, the temperature of the constant temperature heating is 60-100°C; in S2, the temperature of the constant temperature heating is 80-120°C.

9. A salt-assisted inner and outer double-layer carbon-coated silicon material, characterized in that: The silicon material is prepared by the method for preparing the salt-assisted inner and outer double-layer carbon-coated silicon material according to any one of claims 1 to 8.

10. A negative electrode material, characterized in that: It comprises the salt-assisted inner and outer double-layer carbon-coated silicon material as described in claim 9.